Analisis Keunggulan Komparatif Komoditas Kopi - Hendayana, Rachmat; Hutabarat, Budiman; Santoso, Budi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1993)
The share of Indonesian export in world coffee trade in the last five year (1986 to 1990) has grown at slow rate of 1.2 percent per annum. Ever since coffee export quota was frozen in 1989, Indonesian revenue from coffee trade has tended to decline as competition from other countries evolves. The paper investigates the competitive strength of Indonesian coffee produced by state-owned plantation (BUMN), private-owned plantation (PBS), and small-scale farmers (SSF). By applying Domestic Resources Cost Ratio (DRCR) it was concluded that: First, up until production stage, coffee farming by BUMN and PBS result in economic profits which are less than financial profits, while SSF incurs losses. Second, the first two types are relatively efficient in utilizing domestic resources with the values of DRCR at 0.68 and 0.75 respectively; meaning that the systems have comparative advantage in producing coffee bean, while SSF is not efficient with DRCR at 1.07. However, if ivestigation is done through processing stage, the analysis shows that both types are not efficient and, therefore, not competitive. DRCRs for both are 1.24 and 1.56, respectively. Third, it appears that price is the most important factor in determining the feasibility of cofee farming relatif to the price of production inputs such as fertilizer and labour wage. Fourth, in order to improve coffee processing in BUMN and PBS, some effort to deregulate industrial sector that produces machines, and other equipments that are needed in coffee processing activities, and in order to improve small-scale farms performance, extention effort to enhance agronomical and technological skill of farmers needs to be continued.